A legitimidade da jurisdição constitucionalizada para a proteção dos direitos sociais: das tutelas coletivas aos coletivos de tutela - Carvalho, Acelino Rodrigues (Universidade do Vale do Rio dos Sinos, 2013)
The research that led to this thesis aimed to investigate about the possibility of, in the context of contemporary constitutionalism and the institutional limits of the democratic State, conditioning the performance of jurisdiction for the protection of social rights to the prior exhaustion of ordinary democratic institutions. The theoretical framework adopted was the guarantor constitutionalism of Luigi Ferrajoli. What was shown in the course of the investigation was that within this paradigm is enforced a three dimensional view, however, it is found bound to the traditional rule of separation of powers, in addition to acting as a condition of possibility for a greater community role with a view to effecting the social rights. It was concluded that the prior exhaustion of ordinary democratic institutions, through the work of groups and communities of recipients of public services, is the conforming element to democratic legitimacy of jurisdiction for the protection of social rights, because at the same time it preserves the integrity the classical principle of separation of powers, it ensures the space for political democracy in its double dimension: representative and participatory. Moreover, this implies a radicalization in democracy whose consequence is the establishment of a new grammar for the process model of collective actions, operating a reversal in which the emphasis should move from collective tutelage to the collective protection, which increases the potential for fulfillment of social rights.
Keywords: Constitucionalismo contemporâneo; Direitos sociais; Legitimidade democrática; Jurisdição; Participação; Efetivação; Contemporary constitutionalism; Social rights; Democratic legitimacy; Jurisdiction; Participation; Enforcement; ACCNPQ::Ciências Sociais Aplicadas::Direito